(untitled) (International Journal of Biology and Chemistry, 2022)
Chemotherapeutic agents are substances that cure infectious diseases for many years. However, problems arose due to drug resistance that developed over time and it was observed that the drugs failed to kill the bacteria. Studies have been carried out to find the factor caused by drug resistance that adversely affect the disease treatment, and these studies continue today. There are different types of resistance mechanisms. Efflux pumps are just one of these mechanisms. Efflux pumps cannot enter and release the drug into the cell. Thus, the microorganism becomes resistant to the drug used. If this resistance is inhibited, the drug may work. A variety of chemical or natural inhibitors are available for inhibition. However, since they cause toxicity problems, their clinical use is not currently available. Studies in this area are ongoing. There are studies to determine the activity of the efflux pump. The activity of this mechanism can be detected with ethidium bromide (EtBr). In this study, it was aimed to determine the efflux pump activity of some resistant clinically isolated strains using EtBr dye. The strains that are Acinetobacter baumannii, Candida albicans, Candida glabrata, Candida tropicalis, Klebsiella pneumoniae, Providencia rustigianii, Serratia odorifera, Shigella flexneri, Staphylococcus aureus and Streptococcus pneumoniae microorganisms. Cartwheel method was applied on agars containing TSB with EtBr with different concentrations (0.0 mg/L, 0.5 mg/L, 1.0 mg/L, 1.5 mg/L, 2.0 mg/L and 2.5 mg/L). After the incubation, activation case was observed under UV light. It is concluded that each strain used has efflux pump activity. EtBr was released at 0.5 mg/L and did not fluoresce. Different fluorescence were observed under EtBr UV between 1.0 mg/L and 2.5 mg /L.